2018
DOI: 10.4274/tjo.10179
|View full text |Cite
|
Sign up to set email alerts
|

Does Dry Eye Affect Repeatability of Corneal Topography Measurements?

Abstract: Objectives:The purpose of this study was to assess the repeatability of corneal topography measurements in dry eye patients and healthy controls.Materials and Methods:Participants underwent consecutive corneal topography measurements (Sirius; Costruzione Strumenti Oftalmici, Florence, Italy). Two images with acquisition quality higher than 90% were accepted. The following parameters were evaluated: minimum and central corneal thickness, aqueous depth, apex curvature, anterior chamber volume, horizontal anterio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 23 publications
2
14
3
Order By: Relevance
“…Our findings are supported by some other studies: Dogan et al compared the repeatability for a Sirius Scheimpflug device in patients with dry eyes to healthy patients and found excellent agreement of repeated SimK average measurements in both groups. 39 Jensen et al found no statistically significant differences in the K-values of the IOLMaster 700 when comparing repeated measurements with and without different artificial tear drops, although no evaluation of dry eyes was reported. 40 For PCP, both OCT devices had statistically significantly lower means of both average K and astigmatism differences compared to the Scheimpflug device in both groups.…”
Section: Discussionmentioning
confidence: 97%
“…Our findings are supported by some other studies: Dogan et al compared the repeatability for a Sirius Scheimpflug device in patients with dry eyes to healthy patients and found excellent agreement of repeated SimK average measurements in both groups. 39 Jensen et al found no statistically significant differences in the K-values of the IOLMaster 700 when comparing repeated measurements with and without different artificial tear drops, although no evaluation of dry eyes was reported. 40 For PCP, both OCT devices had statistically significantly lower means of both average K and astigmatism differences compared to the Scheimpflug device in both groups.…”
Section: Discussionmentioning
confidence: 97%
“…Meibomian gland dysfunction (MGD)-associated evaporative dry eye negatively affects ocular surface health through tear film instability, increased tear evaporation, hyperosmolarity, inflammation, and subsequent ocular surface damage. 7 , 8 The unstable tear film affects the quality of optical surface reflections from the cornea on which the keratometric measurements are based, compromising keratometry readings with manual keratometry or advanced devices like placido disc/point-source color light-emitting diode topographers, slit-scan imaging, swept source OCT biometers or Scheimpflug image-based tomographers. 9 , 10 Further, chronic ocular desiccation and deficiency of the tears have also been associated with corneal deformation, most commonly inferior corneal steepening and high astigmatism resembling keratoconus.…”
Section: Introductionmentioning
confidence: 99%
“…In previous reports the investigators assessed the repeatability of central corneal thickness (CCC) by Pentacam and corneal topography measurements by Sirius devices [5,6]. Lee et al reported that CCT undulated in dry eyes and found that ICC was lower in dry eyes than healthy eyes by Pentacam [5].…”
Section: Discussionmentioning
confidence: 99%
“…It has been postulated that Scheimpflug device includes the precorneal tear film layer in measuring corneal thickness [4]. Previous studies showed that Pentacam was repeatable in both healthy and dry eyes [1,5,6]. However, a study focusing on the change profile of repeated Pentacam measurements in severe dry eye patients is lacking.…”
Section: Introductionmentioning
confidence: 99%